A java API interface for the search of DTV services in embedded multimedia devices - Lukic, Nemanja; Teslic, Nikola; Maruna, Tomislav; Mihic, Velibor (IEEE transactions on consumer electronics, 2013)
The majority of DTV sets and set top boxes are embedded systems based on Linux. Utilizing network connectivity, they can provide many different kinds of information coming from the Internet such as news, sport events, weather and social networks through a large number of applications that are available for download. Considering the vast amount of data that is available to users, these platforms include specialized applications for unified search and presentation of this data. These applications currently do not support searching of data coming from DTV broadcast stream. This paper presents a proposal for the integration of data coming from DTV broadcast stream into a search mechanism on embedded systems which support the Java programming language. The proposal includes two parts: the Java API specification that is used to access DTV content from search applications, and the DTV native layer API. The latter is used to connect the native code to the Java API and includes approximate string matching technique for reducing spelling errors in search criterion.